STRATEGIES OF RADIO SONORA 98.9 FM TO RETAIN LISTENERS AMID THE RISE OF MUSIC STREAMING APPLICATIONS SPOTIFY - Salma, Deswanda; Triyono, Agus (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This research aims to identify and analyze the strategies of Radio Sonora 98.9 FM Semarang in retaining listeners amid the challenges of the digital era, especially the development of the Spotify music streaming application. This research uses a descriptive qualitative approach with in-depth interview and observation methods to collect data. The results showed that Sonora Radio implemented four main strategies: program suitability, habit formation, listener flow control, and program resource storage. These strategies include scheduling programs according to audience needs, creating advertisements and rundowns to build listening habits, and regular evaluations to improve broadcast quality. In addition, content diversification and innovation, such as collaboration with local influencers and social media optimization, are implemented to attract the younger generation. This research concludes that the success of Radio Sonora's strategy lies in its ability to adapt to the development of digital technology while still maintaining the characteristics of traditional broadcasts that are familiar to listeners.